2021
DOI: 10.7150/ijms.60610
|View full text |Cite
|
Sign up to set email alerts
|

HRC promotes anoikis resistance and metastasis by suppressing endoplasmic reticulum stress in hepatocellular carcinoma

Abstract: Histidine-rich calcium binding protein (HRC) is markedly overexpressed in hepatocellular carcinoma (HCC) and is significantly correlated with metastasis. Anoikis resistance and endoplasmic reticulum (ER) stress may have a critical effect on survival before metastasis. However, the potential functions of HRC in anoikis resistance in HCC remain unknown. Here, we uncovered the clinical value of HRC and its functional significance on anoikis in HCC. The positive expression of HRC was observably correlated with tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Then, these cells will be extruded by neighboring cells through mechanical force, and the extruded cells will undergo anoikis because of the lack of survival signals [ 28 30 ]. Some tumor cells themselves can resist anoikis by upregulating survival signals [ 31 ]. We speculate that if tumor cells of epithelial origin are extruded, they may continue to survive and even metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…Then, these cells will be extruded by neighboring cells through mechanical force, and the extruded cells will undergo anoikis because of the lack of survival signals [ 28 30 ]. Some tumor cells themselves can resist anoikis by upregulating survival signals [ 31 ]. We speculate that if tumor cells of epithelial origin are extruded, they may continue to survive and even metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathways can lead to the acquisition of anoikis resistance in HCC. Xia et al found that histidine-rich calcium binding protein (HRC) could enhance the anoikis resistance and promote the HCC metastasis via protein kinase RNA-like ER kinase (PERK)-eIF2a-ATF4-CHOP signaling axis [7]. Mo et al found that upregulation of IQGAP1 enhanced anoikis resistance, therefore promoting the migration and invasion of HCC cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…As a special type of apoptosis induced by loss of correct cell adhesion, anoikis plays an important role in maintaining the normal integrity of tissues and participates in the invasion and metastasis of tumors, and anoikis resistance is often acquired during tumor progression [3][4][5][6]. A recent study showed that histidine-rich calcium binding protein (HRC) increased the anoikis resistance and promoted the HCC metastasis via the protein kinase RNA like ER kinase (PERK) -eIF2a-ATF4-CHOP signal pathway [7]. In another study, the ability of anoikis resistance of HCC cells was enhanced by inducing autophagy in the acidic environment of HCC, and autophagy inhibitors could reverse the effect of anoikis resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly found by Suhong Xia et al that histidine-rich calcium-binding protein (HRC), an anoikis resistance-associated gene, was also overexpressed in LIHC patients and suggested that this promoted the metastasis of LIHC cells in vivo (Xia et al 2021). Therefore, deciphering the regulatory mechanisms of anoikis resistance would be helpful in improving the clinical management of LIHC.…”
Section: Introductionmentioning
confidence: 87%